Diary of a wimpy kid [compact disc, unabridged] : the getaway - Kinney, Jeff (Kinney, Jeff. Diary of a Wimpy Kid, 2017)
To escape the stress of the holidays, the Heffleys decide to get out of town and go to a resort instead of celebrating Christmas at home. But what's billed as a stress-free vacation becomes a holiday nightmare.